Barriers of Inclusive Education For Children With Disabilities In India: Policies, Challenges, and Recommendations for Inclusive Education of Children with Disabilities in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education is the right of every child because it equips him to meet thechallenges of life. The children with disabilities (CWD) need this all themore, to supplement their differential talents so that they can preparethemselves for a happy productive and useful life. Efforts to educate childrenwith disabilities began soon after independence in India. An attempt has beenmade to examine the policies and legislations for educating the children withdisabilities in India after post- constitution era. In the final section,challenges for providing education to CWD and in that light somerecommendations were made. In India, different definitions of disabilityconditions have been introduced for various purposes, essentially following themedical model and, as such, they have based on various criteria of ascertainingabnormality or pathologic conditions of persons.